When is lift-off? Evaluating forward guidance from the shadow - Matthias Neuenkirch; Pierre L. Siklos (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2014)
Monetary policy decisions are typically taken after a committee has deliberated and voted on a proposal. However, there are well-known risks associated with committee-based decisions. In this paper we examine the record of the shadow Monetary Policy Council in Canada. Given the structure of the committee, how decision-making takes place, as well as the voting arrangements, the MPC does not face the same information cascades and group polarization risks faced by actual decision-makers in central bank monetary policy councils. We find a considerable diversity of opinion about the recommended future path of interest rates inside the MPC. Beginning with the explicit forward guidance provided by the Bank of Canada market determined forward rates diverge considerably from the recommendations implied by the MPC. There is little evidence that the Bank and the MPC coordinate their future views about the interest rate path. However, it is difficult to explain the basis on which median voter inside the MPC, as well as doves and hawks on the committee, change their views about future changes in policy rates. This implies that there remain challenges in understanding the evolution of future interest rate paths over time.
Keywords: E43; E52; E58; E61; E69; 330; Bank of Canada; central bank communication; committee behaviour; monetary policy committees; shadow councils; Taylor rules